Global ecological and economic connections in Arctic and sub-Arctic crab markets. (May 2021) - Kaiser, Brooks A.; Kourantidou, Melina; Ahsan, Dewan; Bakanev, Sergey; Burmeister, AnnDorte; Eckert, Ginny; Fernandez, Linda M.; Hong, Hyun Pyo; Monsalve, Albert Alexandre; Mullowney, Darrell; Nøstvold, Bjørg Helen; Park, Hojeong; et al.
Abstract: High latitude marine systems are experiencing climate change and other human-induced impacts that outpace global averages. Communities dependent on these systems are also undergoing complex economic and socio-ecological changes. Ecological, economic, market and community developments in Arctic and sub-Arctic crab fisheries are increasingly complex and uncertain. These escalating risks and complexities threaten well-being, social and ecological integrity of dependent communities and ecosystems. Through interdisciplinary and transdisciplinary collaboration, we examine the escalation to illustrate how global ecological and economic connections are co-evolving between nature, society, and industry. The article demonstrates how informal, integrative cooperation with broad stakeholder participation at a global scale, focused on information sharing and scientific cooperation, addresses local and regional dynamic markets and ecosystems for improved economic and ecological outcomes. Highlights: Interdisciplinary, international stakeholder cooperation can use information sharing and research collaboration to reduce risks and to improve outcomes for fisheries experiencing rapid and dramatic shifts from climate and other impacts. Ecological and economic interconnections in marine resource production and consumption are clarified and contextualized with application to Arctic and sub-Arctic crab markets. A global scale for cooperation can increasingly benefit local and regional fisheries facing uncertainty from ecological and economic changes.